SEISMIC DESIGN AND BEHAVIOUR OF PRECAST CONCRETE CONNECTIONS FOR ACCELERATED BRIDGE CONSTRUCTION - Luong, Chanh Nien (My University, 2025)
Accelerated Bridge Construction (ABC), which utilizes precast concrete elements, has emerged as a viable alternative to conventional cast-in-place (CIP) methods by reducing construction timelines and enhancing quality control. The success of ABC in seismic regions depends on the performance of precast connections, which is a key focus of this thesis. Precast connections in ABC range from emulative systems, which mimic CIP behaviour, to non-emulative systems, which incorporate controlled rocking for minimized damage. This thesis examines one representative connection from each category: member socket connections (MSC), referred to as MSC piers (emulative), and segmental post-tensioned precast concrete (SPPC) piers (non-emulative). These two systems have different levels of existing knowledge. For SPPC piers, this thesis focuses on defining engineering demand parameter (EDP) drift ratio limits through genetic programming (GP)-based predictive equations, establishing the onset of four damage states. A two-tier performance-based seismic design (PBSD) framework is subsequently developed by integrating displacement-based design and fragility analysis to ensure seismic performance objectives are achieved at both the component and system levels. The framework’s effectiveness is validated through a comparative case study of SPPC piers and conventional CIP piers. For MSC piers, the experimental program was divided into two sets of tests—one at the connection level and another at the pier component level—each targeting a distinct damage mechanism within the MSCs that connects precast columns to spread footings. Test data from connection-level side shear load tests informed the development and validation of a finite-element model that accurately simulates capacity and damage modes under direct shear loading. Meanwhile, quasi-static cyclic tests at the pier component level demonstrated the effectiveness of ultra-high-performance concrete (UHPC) in mitigating diagonal shear damage from prying action, permitting shorter embedment lengths while maintaining connection integrity. Overall, the work presented in this thesis advances the seismic design of precast concrete bridges by providing quantitative EDP limits, a systematic PBSD framework, and experimental validation of precast concrete connections under seismic loading. These outcomes support the broader implementation of ABC in Canada for modern bridge infrastructure in seismic regions.
Keywords: Accelerated Bridge Construction; Emulative Concrete Connection; Non-emulative Concrete Connection; Seismic Design; Seismic Behaviour; Precast Concrete Structures